Drug Utilization and Evaluation of Hmg-co a Reductase Inhibitors in Tertiary Care Teaching Hospital - KG, Praveen; K, Arun (Indian Journal of Pharmacy Practice)
Aprospective study was conducted to evaluate the drug utilization of HMG-CoAreductase inhibitors (statins) in a tertiary care teaching hospital to ensure rational use, safety, prescribing pattern and economic strategy for 6 months, in which 440 patients prescribed with statins were recruited for the study and the data were collected and analyzed statistically. Statins were more prescribed in 60-70 years age group and it was prescribed mainly for primary and secondary prevention of cardiac and cerebro-vascular complications(62.87%) followed by dyslipidemia (29.38%) and hypertriglyceridemia (7.74%). Atorvastatin was more prescribed (85.42%) than Simvastatin (4.78%) and Rosuvastatin (9.79%). Drug-drug interactions were found with digoxin, verapamil and phenytoin. The DDD/12 bed days were found to be 82.32, 2.4, and 15 for the three statins respectively. the prescribed daily dose and the defined daily dose were as follows atorvastatin 19.33mg;20mg, Simvastatin 15.73mg;30mg, and for Rosuvastatin 15.73mg;10mg. The cost of the three statins according to the amount utilized was found to be 4918,302 and 887 rupees respectively. The dosages used for Atorvastatin were generally closer to the maintenance dose recommended by WHO. Whereas a slight difference seen in case of Simvastatin and Rosuvastatin. Though several brands available the least priced statins brands can be selected rather than costlier brands which cause a drastic increase in patient's drug compliance as well as economic status